Understanding complexities of synaptic transmission in medically intractable seizures: A paradigm of epilepsy research - Jyotirmoy Banerjee; Manjari Tripathi; P. Sarat Chandra (Indian Journal of Neurosurgery)
Investigating the changes associated with the development of epileptic state in humans is complex and requires a multidisciplinary approach. Understanding the intricacies of medically intractable epilepsy still remains a challenge for neurosurgeons across the world. A significant number of patients who has undergone resective brain surgery for epilepsy still continue to have seizures. The reason behind this therapy resistance still eludes us. Thus to develop a cure for the difficult to treat epilepsy, we need to comprehensively study epileptogenesis. Although various animal models are developed but none of them replicate the pathological conditions in humans. So the ideal way to understand epileptogenecity is to examine the tissue resected for the treatment of intractable epilepsy. Advanced imaging and electrical localization procedures are utilized to establish the epileptogenic zone in epilepsy patients. Further molecular and cytological studies are required for the microscopic analysis of brain samples collected from the epileptogenic focus. As alterations in inhibitory as well as excitatory synaptic transmission are key features of epilepsy, understanding the regulation of neurotransmission in the resected surgery zone is of immense importance. Here we summarize various modalities of in vitro slice analysis from the resected brain specimen to understand the changes in GABAergic and glutamatergic synaptic transmission in epileptogenic zone. We also review evidence pertaining to the proposed role of nicotinic receptors in abnormal synaptic transmission which is one of the major causes of epileptiform activity. Elucidation of current concepts in regulation of synaptic transmission will help develop therapies for epilepsy cases that cannot me managed pharmacologically.